Expression and Functional Characterization of the RIG-I-Like Receptors MDA5 and LGP2 in Rainbow Trout (Oncorhynchus mykiss) - Chang, Mingxian (American Society for Microbiology, 2011)

(untitled)
The retinoic acid-inducible gene I (RIG-I)-like receptors (RLR) comprise three homologues: RIG-I, melanoma differentiation-associated gene 5 (MDA5), and laboratory of genetics and physiology 2 (LGP2). They activate the host interferon (IFN) system upon recognition of viral RNA pathogen-associated molecular patterns (PAMPs) in the cytoplasm. Bioinformatic analysis of the sequenced vertebrate genomes suggests that the cytosolic surveillance system is conserved in lower vertebrates, and recent functional studies have confirmed that RIG-I is important to fish antiviral immunity. In this study, we have identified MDA5 and LGP2 homologues from rainbow trout Oncorhynchus mykiss and an additional LGP2 variant with an incomplete C-terminal domain of RIG-I. Trout MDA5 and LGP2 were constitutively produced in fibroblast and macrophage cell lines and upregulated by poly(I:C), recombinant IFN, or infection by RNA viruses (viral hemorrhagic septicemia virus and salmon alphavirus) with a single-stranded positive or negative genome. Overexpression of MDA5 and LGP2 but not of the LGP2 variant resulted in significant accumulation of Mx transcripts in cultured cells, which correlated with a marked enhancement of protection against viral infection. These results demonstrate that both MDA5 and LGP2 are important RLRs in host surveillance against infection of both negative and positive viruses and that the LGP2 variant with a deletion of 54 amino acids at the C terminus acts as a negative regulator for LGP2-elicited antiviral signaling by competing for the viral RNA PAMPs. Interestingly, MDA5 expression was not affected by overexpressed LGP2 in transfected cells and vice versa, suggesting that they likely act in parallel as positive regulators for IFN production.